How large databases may impact clinical practices for rare tumors—postoperative chemotherapy in thymic malignancies - Girard, Nicolas; du Vignaux, Claire Merveilleux (Journal of Thoracic Disease, 2016)
In this issue of the Journal of Thoracic Disease, Ma et al. report on the analysis of a cohort of 665 patients with advanced thymic epithelial tumors, looking at the long-term effects of postoperative chemotherapy on recurrence and survival rates (1). This cohort of the Chinese Alliance for Research in Thymomas (ChART) is the largest to date to investigate this question. Postoperative chemotherapy is actually not routine practice (2), as the vast majority of patients operated on for a thymic epithelial tumor do have early-stage disease (1,015 patients out of 2,306 cases in the ChART database), and/or receive primary/induction chemotherapy in the setting of advanced, non-resectable disease to subsequently achieve complete resection (3)—surprisingly a rare situation in the ChART database, only 68 out of 2,306 cases.